How Politics Works : the concepts visually explained - Sturgeon, Alison; DK Publishing, Inc. (New York, NY : DK Publishing, 2022)
"A jargon-free, highly visual guide to every aspect of politics, from political philosophy to 21st-century activism. Discover everything you need to know about political history and thought, and the inner workings of governments around the world with this unique graphic guide."--
Foundations of political thought -- Political theory -- Organizing government -- Political change -- International relations -- Governments around the world.
Includes index.
Keywords: Political science; Political science -- Pictorial works; Politics, Practical; Politics, Practical -- Pictorial works; Political science; Politics, Practical; Instructional and educational works; Instructional and educational works; Illustrated works